PENGARUH KARAKTERISTIK PEKERJAAN DAN PEMBERDAYAAN TERHADAP KINERJA OPERATOR SD NEGERI DI JAKARTA TIMUR - Eni Wahyuni (Universitas Negeri Jakarta, 2015)
The purpose of this research is to determine the effect of job characteristic and empowermen on job performance the personil state primary school in east jakarta. The research methodology was survey which were selected by simple random sampling technique. Analysis and interpretation of the data indicate that (1) job characteristic has a positive direct effect in job perfromance, (2) empowerment has a positive direct effect in job perfformance, (3) job characteristic has a positive direct effect in empowerment.